Application of the TGT (Team Game Tournament) Model for Learning Arabic Maharoh Kalam Class IX DTBS Darussalamah Braja Dewa | Penerapan Model TGT (Team Game Tournament) untuk Pembelajaran Bahasa Arab Kelas IX DTBS Darussalamah Braja Dewa - Latifatul Khusna; Revi Fradita Revita; Muhammad Ainul Yaqin (An-nahdloh : Journal of Arabic Teaching, 2023)
This Study examines the application of the TGT (Team Game Tournament) model for class IX Sudents at DTBS Darussalamah Braja Dewa in learning maharoh Kalam Arabic. This research is interesting to discuss in depth using classroom Action Research (PTK) method, because the problems in this study aim to liven up the atmosphere in the classroom by using the TGT cooperative learning model using 4 stages, namely: planning, implementing actions, observing, and reflecting. By wrapping it in game packaging in groups of 21 students, divided into 4 to 5 people with unequal abilities so that the game takes place in a balanced way. The research instruments used were textbooks, observations, interviews, field notes. The data collection technique is a non-test technique. The non-test technique is carried out through observation sheets and field notes. The results of this study show that the methods used by teachers are less inovative, causing boredom for their students. So that a breakthrough emerged to apply this TGT type learning model as an effort to revive the enthusiasm for learning foreign languanges for class IX DTBS Darussalamah Braja Dewa. The purpose of this writing is to broaden the reader's knowledge about cooperative methods of the Team Games Tournament type and innovations that can be used in learning Maharah Kalam Arabic in class 9 in particular.